Sosialisasi Listrik Aman di Kelurahan Sibatua Kecamatan Pangkajene Kabupaten Pangkep - Burhan, Muh Iswal; Akhyar Muchtar; Elfira Makmur; Hilda Ashari; Laila Sari, Dessy Ana (Fakultas Teknik, Universitas PGRI Banyuwangi, 2022)
Abstract – The problem is based on the frequent occurrence of fires due to short circuits electricity, this is the result of a lack of public understanding regarding the use, selection of correct and safe electrical equipment and the high number of houses that have the potential to catch fire due to old electrical installations more than 20 years, human error, and a house made of wood. Installation Equipment electricity is a solution offered to the community by referring to on General Electrical Installation Requirements (PUIL 2011) for residential houses and the Indonesian National Standard (SNI) for installation equipment. Through this PKM activity, the program carried out is to socialize the use of electrical equipment and the use of electrical energy to avoid overload which can lead to insulation failure resulting in electric short circuit; In this activity, an explanation of the components is givenelectrical installation, how to select, install and maintain.